Tantangan Pemerintah Desa dalam Penyelenggaraan Pelayanan Kesehatan: Studi Kasus di Desa Agung Dalem, Tulang Bawang - Juliette, Aimee (Indonesian Democracy Research Center, 2025)
This study aims to identify the challenges faced by the village government in providing health services in Agung Dalem Village, Banjar Margo District, Tulang Bawang Regency. A qualitative research approach with a case study strategy was employed. The findings indicate that the provision of health services in Agung Dalem Village still encounters significant obstacles. Limited funding constitutes the main barrier to the availability of adequate health facilities and infrastructure. In addition, the shortage of health workers affects both the quality and coverage of services delivered to the village community. The low level of public awareness regarding the importance of health also contributes to delays in disease treatment. These findings are expected to serve as a basis for relevant stakeholders in formulating more effective policies to improve health services in rural areas.